Amateur fishing as a perspective kind of recreation and tourism on water reservoirs of the steppe zone (Journal of Geography and Environmental Management, 2018)
The paper deals with the problems of development of recreationalfishing as an important branch of recreation and tourism on the exampleof the inland water bodies of the steppe zone. Proper organization of thisactivity can provide not only benefits to fish people, but also become ascatalyst for positive changes in the conservation and using of aquatic bioresources,restoration of natural ecosystems, reducing the illegal fishing, toimprove the quality and volume of water environmental ecosystem services.With the development of recreational fishing tourism infrastructure it’snecessary to improve the information management system, what scientificdata should play an important role. An analysis of recreational fishingdataby the example of a large water reservoir in the south of Russia revealeda positive dynamics in the development of this resource, along with theshortcomings of the tourist infrastructure and informationprovision.